God's word for gen alpha: the use of Multimethods to attract interest in the Indonesian Bethel Church in the city of Madya Bogor, West Java - Yulianti, Lidya; Silalahi, Edwin Goklas; Triyanto, Yoel; Rini, Wahyu Astarjo (Technium Social Sciences Journal, 2024)
The church is the center of Christian education in teaching God's word. Through the study of God's words, leaders educate and mature God's people. Therefore, the essence of the church is to provide good Word education, especially among the Alpha generation. The alpha generation, which is growing in the midst of the development of extraordinary information flows, needs to protect its faith from the hedonistic and secular lifestyle of this century. However, in the reality of church ministry that is found today, it turns out that the alpha generation is less interested in learning the Word. A more innovative approach is needed to increase the interest of the alpha generation in learning the word. Based on the above background, the researcher intends to conduct research on the use of Multimethods to increase interest in learning God's word of the alpha generation. This research was held considering the importance of the use of Multimethods which is suspected to be still rarely used in the study of God's Word in the Sunday school of the Indonesian Bethel Church synod in Bogor. From the results of the researchers' observations, it was found that the lack of interest in learning the Word of God was influenced by several factors, which consisted of: the learning process was less interesting, so that it caused a feeling of boredom; and Second, the use of teaching methods that are less varied. Therefore, this study was conducted with the aim of examining how much direct influence the use of Multimethods in teaching God's word on the learning interest of the Alpha generation in the Indonesian Bethel Church in the Municipality of Bogor. This research was conducted using a quantitative approach, using path analysis and survey research methods. The data collection methods used are questionnaires and documentation. This study involved 86 respondents from 102 Sunday school teachers of the Indonesian Bethel Church in the Municipality of Bogor, West Java, using the Krejcie and Morgan formulas. From the results of the study, it was found that: Variable Multimethods has an indirect influence in explaining the variable of Interest in Learning God's Word through Learning Media. The indirect influence of Multimethods on the Interest in Learning God's Word through Learning Media was 64.3%, while the remaining 35.7% was influenced by other factors that were not spoken in the study (epsilon).